The CARMA-NRO Orion survey - Kong, Shuo; Klessen, Ralf S. (The astrophysical journal. Supplement series, 2018)
We present the first results from a new, high-resolution 12CO(1-0), 13CO(1-0), and C18O(1-0) molecular-line survey of the Orion A cloud, hereafter referred to as the CARMA-NRO Orion Survey. CARMA observations have been combined with single-dish data from the Nobeyama 45 m telescope to provide extended images at about 0.01 pc resolution, with a dynamic range of approximately 1200 in spatial scale. Here we describe the practical details of the data combination in uv space, including flux scale matching, the conversion of single-dish data to visibilities, and joint deconvolution of single-dish and interferometric data.